Numerical calculation of current distribution due to spark discharge on water surface with surface potential as boundary condition - Midi, Nur Shahida; Muhamad, Muhammad Khairul Amzar; Ohyama, Ryu-ichiro (The School of Engineering Tokai University, 2014)

(untitled)
Numerical calculations of current distribution due to spark discharge on water surface of 0.07 S/m and 5 S/m conductivity were done using two-dimensional axial-symmetry model. In this work, only the water phase is taken into account as the first step to a complete two-phase gas-liquid model. Electric potential on water surface with filamentary discharge length on water surface obtained from laboratory experiments were used as the boundary condition. The calculations were done under both stationary and time-dependent conditions. Result of stationary calculation shows agreement with the maximum values from time-dependent calculation. Comparison with experimental results also had shown a fairly good agreement. The results discussed were the electric field distribution and the current distribution, then in consequently their relation to each other and to the filamentary discharge observed on the water surface during laboratory experiments. It can be concluded that the distribution of electric field and current is influenced by the filamentary discharge.